2009
DOI: 10.1002/ccd.21836
|View full text |Cite
|
Sign up to set email alerts
|

Results after balloon angioplasty or stenting of atherosclerotic subclavian artery obstruction

Abstract: Endovascular therapy of atherosclerotic subclavian artery obstructions result in excellent acute success rates even in total occlusions. Results evince good durability of endovascular therapy for atherosclerotic occlusive disease of subclavian arteries and with a trend towards better outcome with stenting compared to PTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 30 publications
5
44
1
5
Order By: Relevance
“…Of 107 cases (108 lesions) reported by Sixt et al 9 , the technical success rate was 96% (100% for stenosis (78/78) and 87% for total occlusions (26/30)), treatment modalities included PTA alone (13%) or stenting (87%), and the mortality rate and morbidity rate were both 0%. Patel et al 10 , in a study of 170 cases (177 lesions), reported a technical success rate of 98.3% (99.4% for stenosis (155/156) and 90.5% for occlusions (26/30)), all underwent primary stent placement, and stroke in one patient (0.6%, not described about distal protection of vertebral artery).…”
Section: Discussionmentioning
confidence: 97%
“…Of 107 cases (108 lesions) reported by Sixt et al 9 , the technical success rate was 96% (100% for stenosis (78/78) and 87% for total occlusions (26/30)), treatment modalities included PTA alone (13%) or stenting (87%), and the mortality rate and morbidity rate were both 0%. Patel et al 10 , in a study of 170 cases (177 lesions), reported a technical success rate of 98.3% (99.4% for stenosis (155/156) and 90.5% for occlusions (26/30)), all underwent primary stent placement, and stroke in one patient (0.6%, not described about distal protection of vertebral artery).…”
Section: Discussionmentioning
confidence: 97%
“…[12] retrospectively analyzed 108 interventions of atherosclerotic lesions in subclavian arteries or the brachiocephalic trunk, representing 92% of the patients treated for subclavian artery obstructive disease during a 10-year period. The primary success rate was 97%: 100% for stenoses (78/78) and 87% for total occlusions (26/30).…”
Section: Percutaneous Transluminal Angioplasty Of Supra-aortic Vesselmentioning
confidence: 99%
“…Percutaneous transluminal balloon angioplasty (PTA) and stent implantation for subclavian arterial diseases offer a safer and less invasive alternative to surgery. Recent reports suggested that the initial success, clinical efficacy, and long-term patency of endovascular therapy (EVT) were quite acceptable [4][5][6]. Hence, treatment options have changed during the last three decades and less invasive percutaneous interventions have gained general acceptance.…”
Section: Introductionmentioning
confidence: 99%